Addressing Cross-Cutting Themes in the Use of Education Technology and Digital Learning in Southeast Asia: Recommendations for policy, practice, and research - Swindell, Andrew; Radford, Kate (EdTech Hub, 2025)
Across Southeast Asia, digital learning and EdTech have expanded rapidly in response to long-standing challenges and the Covid-19 pandemic. While access and integration have improved, gaps remain for out-of-school children, girls, learners with disabilities, and those in crisis-affected settings. This paper examines five cross-cutting themes essential to inclusive education: gender equity, special educational needs and disabilities (SEND), school-related violence and bullying, education in emergency and climate-resilient settings, and social and emotional learning (SEL) and mental health and psychosocial support (MHPSS). It offers recommendations for policy, practice, and research to promote flexible, inclusive, and evidence-based approaches to equitable digital learning. Keywords Out-of-school children and youth (OOSCY); Southeast Asia; gender equity; special educational needs and disabilities (SEND); school-related violence and bullying; education in emergencies; social and emotional learning (SEL) An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15270303 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1111 ZenodoArchiveConcept: 15270302
Keywords: _r:AddedByMyEducationEvidence

EdTech for Out-of-School Children and Youth: A Rapid Evidence Review for the Southeast Asian Region - Barnes, Katrina; Mazari, Haani; Mitchell, Joel; Hayat, Amal; Zhao, Annette; Ullah, Noor; Emerusenge, Aime Parfait; D'Rozario, Jonny; Hinks, Jessica; Thinley, Sangay (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) by and for out-of-school children and youth (OOSCY) in Southeast Asia. The review summarises how EdTech is currently being used with OOSCY learners in these contexts, explores how effective these implementations are, and highlights the benefits and challenges of using EdTech with different out-of-school learners. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education for OOSCY, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for OOSCY. Key words: out-of-school children; rapid evidence review; RER; Southeast Asia; ASEAN; education technology; marginalised learners An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10610797 ZenodoArchiveConcept: 10610796 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1007 2339240:SZE9FBW4 2405685:IIAMD77T
Keywords: _r:AddedByMyEducationEvidence